Efisiensi Motor Sinkron Linier dengan Magnet Permanen Sebagai Penggerak KRL Terbaru - Sofitri Rahayu; Yogi Baskoro (Energi & Kelistrikan, 2019)
The latest electric train at this time has begun to be widely used linear synchronous motors with permanent magnets as driving locomotives. This permanent magnet has the same function as a conventional synchronous motor which is to produce a magnetic field so that the motor can move linearly. This linear synchronous motor does not have a gear (gear) and axis, but the mechanical motion of this linear motor is synchronous with the magnetic field running. This running magnetic field is produced by the entanglement of the three phases and the arrangement of magnetic poles U, S, U, S. Because the motor is linear synchronous is a high-speed motor, the mechanical speed is the same as the speed of the magnetic field running. So that this motor is capable of producing large thrust compared to the use of conventional motors (DC motors and induction motors) to drive electric rail trains. If the conventional synchronous motor uses a frequency of 50 Hz, then the linear high-speed synchronous motor uses a frequency of 5-50 Hz in changing its speed and this research the efficiency, electromagnetic power (thrust) and thrust force of a synchronous motor will be analyzed. linear according to the frequency selection from 5-50 Hz, to drive the electric train locomotive.